Devilish Details in Apes and Atoms (The Scientific World Journal)
Nature leads with a preview of an upcoming workshop on sequencing the ape genome. Science leads off this week with a story about a new measurement that comes tantalizingly close to overturning the longstanding Standard Model of particle physics.